The relationship between Ki-67 expression and imaging signs and pathological features in GISTs - Xiao, Lin; Zhang, Yiding; Wang, Yajie; Liu, Lede; Pan, Yisheng (Frontiers in Surgery, 2023)
Introduction: To investigate the correlations between the Ki-67 index and plain-scan computerized tomography (CT) signs and pathological features of gastrointestinal stromal tumor (GIST) tissue. Materials and methods: Data from 186 patients with GIST diagnosed by pathology and immunohistochemistry (IHC) in Peking University First Hospital from May 2016 to May 2022 were analyzed. The patients were divided into two groups: Ki-67≤5% and >5%. Correlation analysis, univariate and multivariate Logistic regression analysis were used to explore the correlations between CT signs, pathological features, and Ki-67 expression. Results: Univariate indicators correlated with the Ki-67 index were mitotic count, pathological grade, tumor hemorrhage, tumor necrosis, tumor size, and tumor density. Multivariate Logistic regression indicated that the mitotic count (odds ratio [OR] 10.222, 95% confidence interval [CI] 4.312-31.039), pathological grade (OR 2.139, 95%CI 1.397-3.350), and tumor size (OR 1.096, 95%CI 1.020-1.190) were independently associated with the Ki-67 expression level. The concordance indexes (C-index) for the pathological features and CT signs models were 0.876 (95%CI 0.822-0.929) and 0.697 (95%CI 0.620-0.774), respectively, with positive predictive values of 93.62% and 58.11% and negative predictive values of 81.29% and 75.89%, respectively. After internal verification by the Bootstrap method, the fitting degree of the pathological features model was found to be better than that of the CT signs model. Conclusions: Mitotic count, pathological risk grading, and tumor size are independent risk factors correlating with high Ki-67 index. These results indicate that the Ki-67 index reflects tumor malignancy and can predict recurrence and metastasis of GIST.